2021
DOI: 10.7554/elife.65683
|View full text |Cite
|
Sign up to set email alerts
|

Distinct protocerebral neuropils associated with attractive and aversive female-produced odorants in the male moth brain

Abstract: The pheromone system of heliothine moths is an optimal model for studying principles underlying higher-order olfactory processing. In Helicoverpa armigera, three male-specific glomeruli receive input about three female-produced signals, the primary pheromone component, serving as an attractant, and two minor constituents, serving a dual function, i.e. attraction versus inhibition of attraction. From the antennal-lobe glomeruli, the information is conveyed to higher olfactory centers, including the lateral prot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 75 publications
0
29
0
Order By: Relevance
“…[5,7,9,13] In addition, we recently demonstrated segregated processing of distinct social cues conveyed along the medial tract of H. armigera males. Specifically, mALT PNs responding to the primary pheromone component predominantly innervates the superior lateral protocerebrum (SLP) and superior intermediate protocerebrum (SIP), whereas mALT PNs sensitive to interspecific signals and the secondary pheromone component (acting as a behavioral antagonist at high concentration) rather innervate anterior parts of the LH (Kymre et al 2021b). In the silkmoth, Bombyx mori, Seki et al (2005) demonstrated that mALT PNs responding to the major pheromone terminate medially of neurons tuned to the minorpheromone.…”
Section: The Medial Altmentioning
confidence: 99%
See 4 more Smart Citations
“…[5,7,9,13] In addition, we recently demonstrated segregated processing of distinct social cues conveyed along the medial tract of H. armigera males. Specifically, mALT PNs responding to the primary pheromone component predominantly innervates the superior lateral protocerebrum (SLP) and superior intermediate protocerebrum (SIP), whereas mALT PNs sensitive to interspecific signals and the secondary pheromone component (acting as a behavioral antagonist at high concentration) rather innervate anterior parts of the LH (Kymre et al 2021b). In the silkmoth, Bombyx mori, Seki et al (2005) demonstrated that mALT PNs responding to the major pheromone terminate medially of neurons tuned to the minorpheromone.…”
Section: The Medial Altmentioning
confidence: 99%
“…Each of these paths thereby appears to connect with all glomerular clusters in the moth AL. Indeed, individual PNs with omniglomerular innervations are found in both the lateral and mediolateral tracts, while the mainly uniglomerular medial-tract PNs collectively cover all glomerular sub-groups (Chu et al 2020b ; Kymre et al 2021a , b ).…”
Section: The Three Main Alts: the Medial Lateral And Mediolateral Tractmentioning
confidence: 99%
See 3 more Smart Citations